Advances in group processes. Vol. 38 - Thye, Shane R.; Lawler, Edward J. (Advances in group processes., 2021)
Advances in Group Processes publishes theoretical analyses, reviews and theory based empirical chapters on group phenomena. This includes work on topics such as status, power, exchange, justice, influence, altruism, decision making, intergroup relations and social networks. Contributors have included scholars from diverse fields including sociology, psychology, political science, economics, biology, philosophy, mathematics and organizational behaviour. Volume 38 brings together papers related to a variety of topics in small groups and organizational research. The volume includes papers that address theoretical and empirical issues related to occupational deference structures, emotions generated by social identities, racial threat, sticky expectations, status and response latency, race and moral expectations in employment, comparison processes and competition and models of intergroup association. Overall, the volume includes papers that reflect a wide range of theoretical approaches from leading scholars who work in the general area of group processes.